P51 Serious pathology mimicking GCA: two cases of carcinoma tongue. (20th April 2020) - kayani, Abdul; Sebastian, Alwin; Borukhson, Liubov; Whitlock, Madeline; Dasgupta, Bhaskar
Abstract: Background: Jaw and tongue pain with constitutional symptoms and raised inflammatory markers are considered pathognomonic ischemic features of giant cell arteritis (GCA). Temporal artery ultrasound (US) (or biopsy) available in GCA fast-track clinics (FTC) for a rapid assessment of patients with suspected GCA. Atypical presentation and negative US or biopsy require further workup to look for an alternative diagnosis. ENT pathology can occur as a mimic of GCA. Herein we discuss two clinical cases of squamous cell cancer tongue presenting with signs and symptoms that resemble GCA. Methods: We have put together a case report. Results: Case-1: A 58-year-old male with a recent presumed diagnosis of relapsing GCA was referred with worsening visual symptoms and right eye pain despite ongoing steroid treatment (60mg), for consideration of Tocilizumab (TCZ). His initial presentation was 5 months ago with a right parietal and retro-orbital headache and blurred vision. He had a normal eye examination. His C-reactive protein (CRP) was raised (24). He was started on prednisolone 40 mg for GCA with complete resolution of symptoms with normalised CRP within weeks. Several weeks later, symptoms reoccurred. CT brain, abdomen and pelvis was normal and temporal artery biopsy negative. His prednisolone was increased to 60 mg. 6 months later, his jaw and tongue pain worsened, and he was treated with pulsed methylprednisolone. Due to partial response to steroids, he was referred to consider TCZ. He had tender left TMJ with normal temporal artery US. Urgent MRI head and neck revealed a left posterior tongue mass with the histology confirmed poorly differentiated squamous cell carcinoma. He was managed with chemo and radiotherapy. Case-2: A 75 years old female, presented with right scalp pain, tongue pain, painful swallowing and chewing. Her blood investigations were normal except a raised ESR (48) and presumed GCA she was started on steroids (60 mg). she had initially good response but, within a few weeks, her symptoms returned. She was then referred to our FTC. Temporal artery US and biopsy were normal. MRI of the head and neck showed a large mass seen in the right half of the posterior tongue extending into the deep aspect of the anterior tongue. Histology confirmed poorly differentiated Squamous cell carcinoma. She was treated with a combination of chemotherapy and radiotherapy. Conclusion: GCA mimics represent a major diagnostic dilemma. FTC helps to stratify the GCA from mimics. Careful evaluation of the history, examination as well as a temporal artery US helps to exclude GCA and aids prompt requesting of appropriate tests to find an alternative diagnosis such as tongue cancers as in our cases. We have now introduced negative weightage for consideration of alternative diagnoses in our GCA probability score. Disclosures: A. Kayani None. A. Sebastian None. L. Borukhson None. M. Whitlock None. B. Dasgupta Consultancies; Roche, Sanofi. Grants/research support; Roche.